An acid digital printing ammonia-nitrogen-free urea substitute, a preparation method and application thereof

CN117926608BActive Publication Date: 2026-10-13SHANGHAI TONA CHEM NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410119082.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2026-10-13
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

[0005]综合各种公开资料,对无氨氮尿素替代剂的研究仍存在不足,尤其是对酸性数码印花无氨氮尿素替代剂研究很少,而针对开发无氨氮尿素替代剂并能降低硫酸铵用量的技术资料更少

Benefits of technology

[0036]本发明提供一种酸性数码印花无氨氮尿素替代剂、其制备方法及用途,本发明无氨氮尿素替代剂应用到酸性数码印花上浆工艺中,能够完全替代尿素,且无氨氮,具有得色高、牢度高、手感好、清晰度高、颜色均匀性好等特性,尤其可在降低硫酸铵用量时具有优异的酸性数码印花效果,综合性能优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117926608B_ABST
    Figure CN117926608B_ABST
Patent Text Reader

Abstract

The application provides an acid digital printing ammonia-nitrogen-free urea substitute, a preparation method and application thereof, and the acid digital printing ammonia-nitrogen-free urea substitute comprises the following components in parts by weight: modifier 35-41 parts by weight; dispersant 1-5 parts by weight; clay 2-5 parts by weight; organic acid 3-7 parts by weight; and deionized water 45-60 parts by weight. The application provides an acid digital printing ammonia-nitrogen-free urea substitute, a preparation method and application thereof, and the ammonia-nitrogen-free urea substitute of the application is applied to an acid digital printing sizing process, can completely replace urea, is free of ammonia-nitrogen, has the characteristics of high color yield, high fastness, good hand feeling, high definition, good color uniformity and the like, and especially has excellent acid digital printing effect when the amount of ammonium sulfate is reduced, and has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of urea substitute and preparation technology, specifically relating to an acidic digital printing ammonia-free urea substitute, its preparation method and uses. Background Technology

[0002] Digital printing is a printing technology that uses digital technology to directly print patterns onto textiles. The basic principle is to use a computer-controlled printhead to spray dye or pigment ink onto the textile to form the desired pattern. Compared to traditional printing, digital printing offers higher precision, richer color expression, and a shorter production cycle. It also boasts advantages such as convenient and fast production, cost savings, and the ability to process multiple patterns in small batches. Acidic digital printing is generally used for printing on fabrics such as silk and nylon. Most acidic dyes in acidic inks contain sulfonic acid groups, hydroxyl groups, etc., and a few are sodium carboxylate salts that ionize in water to form pigment anions. These anions are water-soluble, have bright colors, and a complete color spectrum. They can combine with amino or amide groups on fibers, thus making them suitable for digital printing on wool, silk, and nylon fabrics.

[0003] Acidic digital printing typically involves sizing the fabric before the actual printing process, which includes printing, drying, steaming, and washing. Sizing is the primary step in acidic digital printing and directly affects its final result. The sizing method generally involves dissolving components such as digital printing paste, urea, and ammonium sulfate, and then applying them to the fabric via padding. The printing paste is a synthetic or natural polymer compound with thickening and water-retaining properties, significantly impacting the color yield and clarity of acidic digital printing. Urea has hygroscopic, swelling, and solubilizing effects; ammonium sulfate provides acidic conditions for color fixation and uniformity. However, the excessive use of urea and ammonium sulfate in acidic digital printing sizing agents leads to severely excessive ammonia nitrogen emissions in dyeing wastewater. Addressing this ammonia nitrogen emission problem is urgent, and the development of ammonia-free urea substitutes for acidic digital printing is a current trend in the printing industry and a hot research topic.

[0004] To reduce ammonia nitrogen emissions, researchers have conducted extensive work. For example, CN112323514A discloses a urea substitute with high color yield, but this substitute contains an amide component, still containing ammonia nitrogen. Furthermore, it is applied to traditional reactive printing processes, offering limited guidance for ammonia-free urea substitutes in acidic digital printing. CN109594364A describes an ammonia-free urea substitute, but the preparation process for some components is complex, and its application in reactive printing offers little guidance for acidic digital printing. CN112080955A uses a urea substitute, but this component contains ammonia nitrogen and is used in reactive digital printing, and urea is also used in the pulping process; therefore, it does not fundamentally solve the problem of reducing ammonia nitrogen.

[0005] Based on publicly available information, research on ammonia-free urea substitutes remains insufficient, particularly regarding those for acidic digital printing. Even less research exists on developing ammonia-free urea substitutes that can reduce ammonium sulfate usage. Therefore, it is essential to develop an ammonia-free urea substitute for acidic digital printing on nylon fabrics to effectively reduce ammonia nitrogen emissions, improve printing results, and promote technological advancements in digital printing. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides an acidic digital printing ammonia-free urea substitute, its preparation method, and its uses, which can effectively solve the above-mentioned problems.

[0007] The technical solution adopted in this invention is as follows:

[0008] One aspect of the present invention provides an acidic digital printing ammonia-free urea substitute, comprising the following components in parts by weight:

[0009] 35-41 parts by weight of modifier

[0010] 1-5 parts by weight of dispersant

[0011] 2-5 parts by weight of clay

[0012] 3-7 parts by weight of organic acids

[0013] 45-60 parts by weight of deionized water.

[0014] Preferably, the modifier has an average molecular weight of 1140~2020 and the structural formula is as follows:

[0015]

[0016] in:

[0017] R represents an alkyl group, and the structure is as follows: a=9, 11;

[0018] n=1, 2; m=8~20.

[0019] Preferably, the dispersant is sodium carboxymethyl cellulose or carboxymethyl guar gum.

[0020] Preferably, the sodium carboxymethyl cellulose has a viscosity of 10-50 mPa·s and a degree of substitution of 1.2-1.5 at 1%; and the carboxymethyl guar gum has a viscosity of 10-50 mPa·s and a degree of substitution of 0.3-0.7 at 1%.

[0021] Preferably, the clay is one of sodium bentonite or attapulgite, and the clay particle size is 50~150nm.

[0022] Preferably, the organic acid is one or a mixture of several of citric acid, tartaric acid and lactic acid.

[0023] Another aspect of the present invention provides a method for preparing the aforementioned acidic digital printing ammonia-free urea substitute, comprising the following steps:

[0024] Step 1: Prepare the modifier;

[0025] Step 2: Mix the prescribed amount of dispersant and the prescribed amount of deionized water, and shear at 800~1500 rpm for 2 hours to obtain the dispersant solution;

[0026] Step 3: Add the prescribed amount of clay to the dispersant solution obtained in Step 2, increase the rotation speed to 1500~2000 rpm, and perform high-speed shearing for 30 minutes to obtain a dispersant clay suspension.

[0027] Step 4: After obtaining the dispersant clay suspension from Step 3, reduce the stirring speed to 50-100 rpm, add the amount of modifier specified in the formula, then add the amount of organic acid specified in the formula to neutralize the pH value to 4-6, and continue stirring for 30 minutes to prepare the acidic digital printing ammonia-free urea substitute.

[0028] Preferably, in step 1, the modifier is synthesized from a solid alkyl glycoside and polyethylene glycol diglycidyl ether under the action of a catalyst, and the reaction formula is as follows:

[0029]

[0030] Wherein: the molar ratio of solid alkyl glycoside to polyethylene glycol diglycidyl ether is 1:1 to 1:0.9, the catalyst is potassium hydroxide or sodium hydroxide, and the amount of catalyst is 0.25% to 1% of the total mass of the reactants formed by solid alkyl glycoside and polyethylene glycol diglycidyl ether.

[0031] Preferably, the method for preparing the modifier includes:

[0032] Step 1.1: Mix the prescribed amounts of solid alkyl glycoside, polyethylene glycol diglycidyl ether, and catalyst to obtain a mixture;

[0033] Step 1.2: Heat the mixture to 120℃~140℃ and stir at 80 rpm for 6 hours. Then cool it down to 50℃, add deionized water, and continue stirring for 30 minutes to obtain a modifier with a mass fraction of 50%~70%. The amount of deionized water added is such that the mass fraction of the prepared modifier is in the range of 50%~70%.

[0034] Another aspect of the present invention provides the use of the aforementioned acidic digital printing ammonia-free urea substitute, wherein the acidic digital printing ammonia-free urea substitute is used as a raw material for preparing an acidic digital printing sizing agent, thereby obtaining an acidic digital printing sizing agent.

[0035] The present invention provides an ammonia-free urea substitute for acidic digital printing, its preparation method, and its uses, which have the following advantages:

[0036] This invention provides an ammonia-free urea substitute for acidic digital printing, its preparation method, and its uses. When applied to the sizing process of acidic digital printing, this ammonia-free urea substitute can completely replace urea and is ammonia-free. It has the characteristics of high color yield, high fastness, good hand feel, high clarity, and good color uniformity. In particular, it can achieve excellent acidic digital printing effect when reducing the amount of ammonium sulfate, and has excellent overall performance. Attached Figure Description

[0037] Figure 1 A schematic flowchart illustrating the preparation method of the acidic digital printing ammonia-free urea substitute provided by the present invention. Detailed Implementation

[0038] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the invention.

[0039] This invention provides an ammonia-free urea substitute for acidic digital printing, its preparation method, and its uses. When applied to the sizing process of acidic digital printing, this ammonia-free urea substitute can completely replace urea and is ammonia-free. It has the characteristics of high color yield, high fastness, good hand feel, high clarity, and good color uniformity. In particular, it can achieve excellent acidic digital printing effect when reducing the amount of ammonium sulfate, and has excellent overall performance.

[0040] This invention provides an acidic digital printing ammonia-nitrogen-free urea substitute, comprising the following components in parts by weight:

[0041] 35-41 parts by weight of modifier

[0042] 1-5 parts by weight of dispersant

[0043] 2-5 parts by weight of clay

[0044] 3-7 parts by weight of organic acids

[0045] 45-60 parts by weight of deionized water.

[0046] In this invention, the modifier has an average molecular weight of 1140~2020 and the structural formula is as follows:

[0047]

[0048] in:

[0049] R represents an alkyl group, and the structure is as follows: a=9, 11;

[0050] n=1, 2; m=8~20.

[0051] In one embodiment of the present invention, the dispersant is sodium carboxymethyl cellulose or carboxymethyl guar gum, wherein 1% sodium carboxymethyl cellulose has a viscosity of 10~50 mPa·s and a degree of substitution of 1.2~1.5; and 1% carboxymethyl guar gum has a viscosity of 10~50 mPa·s and a degree of substitution of 0.3~0.7.

[0052] In one embodiment of the present invention, the clay is either sodium bentonite or attapulgite, and the clay particle size is 50~150nm.

[0053] In one embodiment of this invention, the organic acid is one or a mixture of several of citric acid, tartaric acid, and lactobionic acid.

[0054] This invention also provides a method for preparing an ammonia-free urea substitute for acidic digital printing, comprising the following steps:

[0055] Step 1: Prepare the modifier;

[0056] In this step, the modifier is synthesized from solid alkyl glycoside and polyethylene glycol diglycidyl ether under the action of a catalyst, and the reaction formula is as follows:

[0057]

[0058] Wherein: the molar ratio of solid alkyl glycoside to polyethylene glycol diglycidyl ether is 1:1 to 1:0.9, the catalyst is potassium hydroxide or sodium hydroxide, and the amount of catalyst is 0.25% to 1% of the total mass of the reactants formed by solid alkyl glycoside and polyethylene glycol diglycidyl ether.

[0059] The specific methods for preparing the modifier include:

[0060] Step 1.1: Mix the prescribed amounts of solid alkyl glycoside, polyethylene glycol diglycidyl ether, and catalyst to obtain a mixture;

[0061] Step 1.2: Heat the mixture to 120℃~140℃ and stir at 80 rpm for 6 hours. Then cool it down to 50℃, add deionized water, and continue stirring for 30 minutes to obtain a modifier with a mass fraction of 50%~70%. The amount of deionized water added is such that the mass fraction of the prepared modifier is in the range of 50%~70%.

[0062] Step 2: Mix the prescribed amount of dispersant and the prescribed amount of deionized water, and shear at 800~1500 rpm for 2 hours to obtain the dispersant solution;

[0063] Step 3: Add the prescribed amount of clay to the dispersant solution obtained in Step 2, increase the rotation speed to 1500~2000 rpm, and perform high-speed shearing for 30 minutes to obtain a dispersant clay suspension.

[0064] Step 4: After obtaining the dispersant clay suspension from Step 3, reduce the stirring speed to 50-100 rpm, add the amount of modifier specified in the formula, then add the amount of organic acid specified in the formula to neutralize the pH value to 4-6, and continue stirring for 30 minutes to prepare the acidic digital printing ammonia-free urea substitute.

[0065] The present invention also provides the use of an acidic digital printing ammonia-free urea substitute, wherein the acidic digital printing ammonia-free urea substitute is used as a raw material for preparing an acidic digital printing sizing agent, thereby preparing an acidic digital printing sizing agent.

[0066] This invention, based on the principles of urea's dilution, solubilization, and color-fixing effects, prepares a urea substitute with excellent acidic digital printing performance and no ammonia nitrogen content. The main characteristics and functions of each component are as follows:

[0067] (1) Modifier: The modifier in this invention uses a special long-chain polyether to link two alkyl glycoside molecules together. The -CH2CH2O- and -OH groups in the structure have good binding properties with acid dyes, and the strong permeability of the alkyl glycoside structure allows the large molecules after binding the dye to penetrate into the fiber, so that the dye can fully dye the fiber. The water solubility of the modifier ensures that it will not remain on the fiber after soaping, so as not to affect the quality of acid digital printing.

[0068] (2) Clay: Clay components can adsorb a large number of dye molecules and work synergistically with modifiers, so that higher concentrations of dye are adsorbed on the fiber surface. Under the action of concentration difference, the dye further penetrates and fixes the fiber, improving the printing depth.

[0069] (3) Dispersant: The dispersant components not only have a good dispersing effect on urea substitute products, making the products stable, but also have a good dispersing effect on dyes, dye-clay complexes, and dye-modifier complexes, preventing color spots and color patterns, and ensuring that the printing uniformity and color brightness meet the standards.

[0070] (4) Organic acids: Ammonia-free organic acids can provide an acidic environment, which can not only improve the fixation of acid dyes on fibers, but also reduce the amount of ammonium sulfate used while ensuring the effect of acid digital printing, thereby further reducing the ammonia nitrogen emissions in the acid digital printing process.

[0071] The present invention will be further described in detail below with reference to embodiments:

[0072] Example 1:

[0073] Based on the total weight of the ammonia-free urea substitute for acidic digital printing, the mass fraction of each component is as follows:

[0074] Solid alkyl glycosides (n=1, a=9) 19.99%

[0075] Potassium hydroxide 0.36%

[0076] Polyethylene glycol diglycidyl ether (m=500) 15.6%

[0077] Sodium carboxymethyl cellulose 1%

[0078] (1% viscosity is 50 mPa·s, degree of substitution DS. 1.5)

[0079] 3% sodium bentonite

[0080] Citric acid 4.5%

[0081] 55.55% deionized water

[0082] Preparation of Modifier A:

[0083] In reactor #1, 19.99 g of solid alkyl glycoside, 0.36 g of potassium hydroxide, and 15.6 g of polyethylene glycol diglycidyl ether were mixed, heated to 120 °C, and stirred at 80 rpm for 4 hours. The mixture was then cooled to 50 °C, and 36 g of deionized water was added. Stirring continued for 30 minutes to obtain 72 g of modifier A with a mass fraction of 50%. The average molecular weight of modifier A was 1140.

[0084] Preparation of urea substitute A:

[0085] In reactor #2, 1g of sodium carboxymethyl cellulose was mixed with 19.5g of deionized water and stirred at 800rpm for 2 hours. Then, 3g of sodium bentonite was added, and the stirring speed was increased to 1500rpm. The mixture was stirred at high speed for 30 minutes. Then, the stirring speed was reduced to 100rpm, and 72g of modifier A prepared in reactor #1 was added. Finally, 4.5g of citric acid was added to neutralize the pH to 4-6, and the mixture was stirred for another 30 minutes to obtain 100g of urea substitute A with a mass fraction of 44.5%.

[0086] Example 2

[0087] Based on the total weight of the ammonia-free urea substitute for acidic digital printing, the mass fraction of each component is as follows:

[0088] Solid alkyl glycosides (n=1, a=9) 20%

[0089] Potassium hydroxide 0.27%

[0090] Polyethylene glycol diglycidyl ether (m=600) 18.8%

[0091] Sodium carboxymethyl cellulose 1%

[0092] (1% viscosity is 30 mPa·s, degree of substitution DS. 1.5)

[0093] Sodium bentonite 2%

[0094] Lactobionic acid 6.93%

[0095] 51% deionized water

[0096] Preparation of modifier C:

[0097] In reactor #1, 20g of solid alkyl glycoside, 0.27g of potassium hydroxide, and 18.8g of polyethylene glycol diglycidyl ether were mixed, heated to 140℃, and stirred at 80rpm for 4 hours. The mixture was then cooled to 50℃, and 32g of deionized water was added. Stirring continued for 30 minutes to obtain 71g of modifier C with a mass fraction of 55%. The average molecular weight of modifier C was 1240.

[0098] Preparation of urea substitute C:

[0099] In reactor #2, 1g of sodium carboxymethyl cellulose was mixed with 19g of deionized water and stirred at 800rpm for 2 hours. Then, 2g of sodium bentonite was added, and the stirring speed was increased to 1500rpm. The mixture was stirred at high speed for 30 minutes, and then the stirring speed was reduced to 100rpm. 71g of the modifier C prepared in reactor #1 was added, and finally 6.93g of lactobionic acid was added to neutralize the pH to 5-7. The mixture was stirred for another 30 minutes to obtain 100g of urea substitute C with a mass fraction of 49.05%.

[0100] Example 3

[0101] Based on the total weight of the ammonia-free urea substitute for acidic digital printing, the mass fraction of each component is as follows:

[0102] Solid alkyl glycosides (n=2, a=9) 20%

[0103] Sodium hydroxide 0.28%

[0104] Polyethylene glycol diglycidyl ether (m=800) 14.9%

[0105] Sodium carboxymethyl cellulose 0.3%

[0106] (1% viscosity is 10 mPa·s, degree of substitution DS. 1.2)

[0107] attapulgite 2%

[0108] Citric acid 3%

[0109] Deionized water 59.52%

[0110] Preparation of Modifier D:

[0111] In reactor #1, 20g of solid alkyl glycoside, 0.28g of sodium hydroxide, and 14.9g of polyethylene glycol diglycidyl ether were mixed, heated to 120℃, and stirred at 80rpm for 6 hours. The mixture was then cooled to 50℃, and 35.18g of deionized water was added. Stirring continued for 30 minutes to obtain 70.36g of modifier D with a mass fraction of 50%. The average molecular weight of modifier D was 1764.

[0112] Preparation of urea substitute D:

[0113] In reactor #2, 0.3g of sodium carboxymethyl cellulose was mixed with 24.34g of water and stirred at 800rpm for 2 hours. Then, 2g of attapulgite was added, and the stirring speed was increased to 1500rpm. The mixture was stirred at high speed for 30 minutes, and then the stirring speed was reduced to 100rpm. 70.36g of modifier solution D was added, and finally, 3g of citric acid was added to neutralize the pH to 4-6. The mixture was stirred for another 30 minutes to obtain 100g of urea substitute D with a concentration of 40.48%.

[0114] Example 4

[0115] Based on the total weight of the ammonia-free urea substitute for acidic digital printing, the mass fraction of each component is as follows:

[0116] Solid alkyl glycosides (n=2, a=11) 20.5%

[0117] Potassium hydroxide 0.2%

[0118] Polyethylene glycol diglycidyl ether (m=1000) 20%

[0119] Carboxymethyl guar gum 0.3%

[0120] (1% viscosity is 30 mPa·s, degree of substitution is 0.7)

[0121] Attapulgite 2.8%

[0122] Tartaric acid 4.5%

[0123] Deionized water 51.7%

[0124] Preparation of Modifier E:

[0125] In reactor #1, 20.5 g of solid alkyl glycoside, 0.2 g of potassium hydroxide, and 20 g of polyethylene glycol diglycidyl ether were mixed, heated to 130 °C, and stirred at 80 rpm for 4 hours. The mixture was then cooled to 50 °C, and 22 g of deionized water was added. Stirring continued for 30 minutes to obtain 63 g of modifier E with a mass fraction of 65%. The average molecular weight of modifier E was 2020.

[0126] Preparation of urea substitute E

[0127] In reactor #2, 0.3g of carboxymethyl guar gum was mixed with 29.7g of deionized water and stirred at 800rpm for 2 hours. Then, 2.8g of attapulgite was added, and the stirring speed was increased to 1500rpm. The mixture was stirred at high speed for 30 minutes, and then the stirring speed was reduced to 100rpm. 63g of modifier E prepared in reactor #1 was added, and finally 4.5g of tartaric acid was added to neutralize the pH to 4-6. The mixture was stirred for another 30 minutes to obtain 100g of urea substitute E with a mass fraction of 48.25%.

[0128] The advantages of this invention compared to traditional solutions are verified through the following examples:

[0129] (a) Acidic digital printing process

[0130] In this verification example, the fabric used is nylon knitted fabric, and the acidic digital printing process used is as follows: sizing (pad sizing agent, one dip and one pad) → drying (150℃, 1min) → acidic digital printing → drying (100℃, 2min) → washing → soaping (TANAJET Wash ASP 1g / L, soda ash 1g / L) → washing → drying.

[0131] (II) Performance Testing Methods for Acid-Induced Digital Printed Fabrics

[0132] In this verification example, the performance testing method for acid-printed digital fabrics is as follows:

[0133] (1) Apparent color gain

[0134] The intensity value of acid-based digitally printed fabrics was tested using a Datacolor colorimeter. The average value was taken from three test points. The intensity value of a certain fabric color was set at 100. The higher the value, the higher the apparent color gain, and vice versa.

[0135] (2) Fastness

[0136] (2.1) Wash fastness

[0137] Referring to the GB / T 3921-2008 standard, the acidic digital printed fabric sample was sewn together with a standard lining, placed in a prepared soap solution, mechanically stirred at a specified temperature and time, and then washed and dried. The staining effect of the lining was evaluated using the original sample as a reference.

[0138] (2.2) Color fastness to rubbing

[0139] Using the GB / T 3920-2008 standard, the degree of staining from the acidic digitally printed fabric sample was assessed by rubbing it against a dry rubbing cloth and a wet rubbing cloth.

[0140] (3) Printed feel

[0141] Five people touched the acid-printed digital fabric and rated its hand feel, with 5 being the softest and 1 being the softest.

[0142] (4) Clarity (bleed width)

[0143] Under an XYM metallographic video microscope, the edge morphology of patterns obtained under different printing parameters was observed at 100x magnification. The clarity of the acid digital printing pattern was evaluated by measuring the maximum width D of the edge bleeding of the printed pattern. The larger the bleeding width, the worse the clarity of the pattern.

[0144] (5) Printing uniformity

[0145] (5.1) Using a certain point on the fabric as a standard, test the color intensity values ​​at 20 locations on the fabric, and then calculate the average absolute deviation of the values. The larger the average absolute deviation, the greater the data dispersion and the less uniform the printed fabric sample. Conversely, the smaller the average absolute deviation, the more uniform the sample.

[0146] (5.2) The uniformity of the printed fabric sample was visually inspected by 5 people and rated on a scale of 1 to 5, with 5 being the best uniformity and 1 being the worst.

[0147] Comparative Example 1:

[0148] This comparative example is used to examine the performance differences of acidic digitally printed fabrics prepared using different urea substitutes or urea, with all other process parameters being the same, to demonstrate that the urea substitute of the present invention performs better than conventional urea substitutes and urea.

[0149] 1. Test method:

[0150] An acidic digital printing sizing agent was prepared by using 3% auxiliaries, 3% ammonium sulfate, 2% TANAJET Prep APW 01 sizing agent, and the balance being water, based on a mass fraction. The acidic digital printing process was then used to obtain acidic digital printed fabrics.

[0151] As experimental groups 1 to 4, the auxiliaries were prepared using urea substitute A, urea substitute C, urea substitute D and urea substitute E respectively according to Examples 1 to 4 of the present invention. The acidic digital printing fabrics prepared therefrom are respectively denoted as acidic digital printing fabric A1, acidic digital printing fabric C1, acidic digital printing fabric D1 and acidic digital printing fabric E1.

[0152] As control group 1, the auxiliary agent used was a commercially available conventional urea substitute, denoted as commercially available conventional urea substitute F. The acidic digital printing fabric prepared in this way was denoted as acidic digital printing fabric F1.

[0153] As control group 2, commercially available conventional urea was used as the auxiliary agent, and the acidic digital printing fabric prepared in this way was denoted as acidic digital printing fabric G1.

[0154] Specific preparation parameters are shown in Table 1, and the content of each component is a mass percentage:

[0155] Table 1:

[0156] 2. Performance Testing:

[0157] Performance tests were conducted on acid-printed digital fabrics A1, C1, D1, E1, F1, and G1. The results are shown in Table 2.

[0158] Table 2 Properties of acid-printed fabrics prepared by different methods

[0159] As shown in Table 2, the acidic digital printing fabrics A1, C1, D1, and E1 prepared using urea substitutes in experimental groups 1 to 4 of this invention, compared with the acidic digital printing fabric G1 prepared based on commercially available conventional urea in control group 2, exhibit 5%-15% higher color yield. Furthermore, the wash fastness, rubbing fastness, and hand feel of the acidic digital printing fabrics A1, C1, D1, and E1 prepared using urea substitutes in experimental groups 1 to 4 of this invention are comparable to those prepared using commercially available conventional urea, with slightly better clarity. This demonstrates that the urea substitute prepared in this invention is superior to commercially available conventional urea; moreover, compared to commercially available conventional urea, the urea substitute of this invention is an ammonia-free urea substitute.

[0160] The acidic digital printing fabrics A1 to E1 prepared in experimental groups 1 to 4 of this invention, compared with the acidic digital printing fabric F1 prepared in control group 1 based on commercially available conventional urea substitute F, showed that the present invention achieved a color depth of 10-40%, a dry friction height of 0.5, a wet friction height of 1.5, a better hand feel of 0.5, and higher clarity (with a 54-65% lower penetration width). This demonstrates that the urea substitute prepared in this invention is superior to commercially available conventional urea substitutes.

[0161] This demonstrates that the acidic digital printing fabric prepared using the urea substitute of the present invention has better performance than the acidic digital printing fabric prepared using commercially available conventional urea substitutes or commercially available conventional urea.

[0162] Comparative Example 2:

[0163] This comparative example was used to examine the performance differences of acidic digitally printed fabrics prepared using different urea substitutes or urea, and with the ammonium sulfate dosage adjusted while other process parameters remained the same. It was demonstrated that the urea substitute of the present invention outperforms conventional urea substitutes and urea.

[0164] 1. Test method:

[0165] The preparation process was the same as that used in Comparative Example 1. The amounts of each component and the names of the resulting acidic digital printed fabrics are shown in Table 3.

[0166] Table 3:

[0167] In comparison, the components and amounts used in control group 4 and control group 2 in comparative example 1 are the same. Therefore, the acidic digital printing fabric G2 prepared by control group 4 and the acidic digital printing fabric G1 prepared by control group 2 are the same products.

[0168] 2. Performance Testing:

[0169] Performance tests were conducted on acid-printed digital fabrics A2, C2, D2, E2, F2, and G2. The results are shown in Table 4.

[0170] Table 4. Properties of acid-printed fabrics prepared by different methods

[0171] As shown in Table 4, the acidic digital printed fabrics A2, C2, D2, and E2 prepared in experimental groups 5 to 8 of this invention, compared with the acidic digital printed fabric G2 prepared based on commercially available conventional urea in control group 4, exhibit comparable performance in terms of apparent color yield, wash fastness, wet and dry rubbing, hand feel, and clarity for C, M, Y, and K colors. Furthermore, the amount of ammonium sulfate used in experimental groups 5 to 8 of this invention is lower than that used in control group 4. This indicates that the application of the urea substitute of this invention, while reducing the amount of ammonium sulfate, does not reduce the performance indicators, thus proving that the urea substitute of this invention is superior to commercially available conventional urea.

[0172] Compared with acidic digital printing fabrics A2 to E2 prepared in experimental groups 5 to 8 of this invention, acidic digital printing fabric F2 prepared in control group 3 based on commercially available conventional urea substitute F showed that the color of acidic digital printing fabric F2 was 15-20% lighter than that of this invention, and its wash fastness, wet and dry rubbing were 0.5-1 grades lower, its hand feel was 1.5 grades lower, its clarity was worse (the diffusion width was 20-23 μm higher), and its printing uniformity was 2 grades lower. Therefore, when using the same amount of ammonium sulfate, the acidic digital printing fabric prepared by this invention has better performance than the acidic digital printing fabric prepared based on commercially available conventional urea substitute F. This proves that the urea substitute of this invention is superior to commercially available conventional urea substitutes.

[0173] Based on the data in Tables 2 and 4, the key printing effects of this invention, including color yield, wash fastness, wet and dry rubbing, hand feel, clarity, and printing uniformity, all reach ideal levels. When the amount of ammonium sulfate used in experimental groups 1 to 4 was reduced from 3% to 1% in experimental groups 5 to 8, the acidic digital printing effect still achieved the same results as when using commercially available urea with 3% ammonium sulfate. Therefore, the urea substitute of this invention can not only completely replace urea but also significantly reduce the amount of ammonium sulfate component, which has a high ammonia nitrogen content, resulting in a significant reduction in ammonia nitrogen emissions from acidic digital printing.

[0174] The urea substitute component of this invention contains a modifier that adsorbs and binds to acidic dyes, as well as clay, which allows the dye on the fabric surface to reach a high concentration during printing. Under the action of the penetrating component, the dispersing component, and the organic acid, the dye completely and uniformly penetrates into the fiber and is fixed during steaming. Ultimately, the dye achieves ideal results in terms of color yield, fastness, hand feel, printing uniformity, and clarity.

[0175] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An ammonia-free urea substitute for acidic digital printing, characterized in that, The components include the following parts by weight: 35-41 parts by weight of modifier 1-5 parts by weight of dispersant 2-5 parts by weight of clay 3-7 parts by weight of organic acids 45-60 parts by weight of deionized water The modifier has an average molecular weight of 1140~2020 and its structural formula is as follows: ; in: R represents an alkyl group, and the structure is as follows: a=9, 11; n=1, 2; m=8~20.

2. The acid-free urea substitute for digital printing according to claim 1, characterized in that, The dispersant is sodium carboxymethyl cellulose or carboxymethyl guar gum.

3. The acid-free urea substitute for digital printing according to claim 2, characterized in that, The sodium carboxymethyl cellulose has a viscosity of 10-50 mPa·s and a degree of substitution of 1.2-1.5 at 1% concentration; the carboxymethyl guar gum has a viscosity of 10-50 mPa·s and a degree of substitution of 0.3-0.7 at 1% concentration.

4. The acid-free urea substitute for digital printing according to claim 1, characterized in that, The clay is either sodium bentonite or attapulgite, and the clay particle size is 50~150nm.

5. The acid-free urea substitute for digital printing according to claim 1, characterized in that, The organic acid is one or a mixture of several of citric acid, tartaric acid, and lactic acid.

6. A method for preparing an acidic digital printing ammonia-free urea substitute according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: Prepare the modifier; Step 2: Mix the prescribed amount of dispersant and the prescribed amount of deionized water, and shear at 800~1500 rpm for 2 hours to obtain the dispersant solution; Step 3: Add the prescribed amount of clay to the dispersant solution obtained in Step 2, increase the rotation speed to 1500~2000 rpm, and perform high-speed shearing for 30 minutes to obtain a dispersant clay suspension. Step 4: After obtaining the dispersant clay suspension from Step 3, reduce the stirring speed to 50-100 rpm, add the amount of modifier specified in the formula, then add the amount of organic acid specified in the formula to neutralize the pH value to 4-6, and continue stirring for 30 minutes to prepare the acidic digital printing ammonia-free urea substitute.

7. The preparation method of the acidic digital printing ammonia-free urea substitute according to claim 6, characterized in that, In step 1, the modifier is synthesized from solid alkyl glycoside and polyethylene glycol diglycidyl ether under the action of a catalyst, and the reaction formula is as follows: ; Wherein: the molar ratio of solid alkyl glycoside to polyethylene glycol diglycidyl ether is 1:1 to 1:0.9, the catalyst is potassium hydroxide or sodium hydroxide, and the amount of catalyst is 0.25% to 1% of the total mass of the reactants formed by solid alkyl glycoside and polyethylene glycol diglycidyl ether.

8. The preparation method of the acidic digital printing ammonia-free urea substitute according to claim 7, characterized in that, Methods for preparing modifiers include: Step 1.1: Mix the prescribed amounts of solid alkyl glycoside, polyethylene glycol diglycidyl ether, and catalyst to obtain a mixture; Step 1.2: Heat the mixture to 120℃~140℃ and stir at 80 rpm for 4~6 hours. Then cool it down to 50℃, add deionized water, and continue stirring for 30 minutes to obtain a modifier with a mass fraction of 50%~70%. The amount of deionized water added is such that the mass fraction of the prepared modifier is in the range of 50%~70%.

9. The use of the acidic digital printing ammonia-free urea substitute according to any one of claims 1 to 5, characterized in that, The ammonia-free urea substitute for acidic digital printing is used as a raw material for preparing acidic digital printing sizing agent, thereby obtaining the acidic digital printing sizing agent.

Citation Information

Patent Citations

  • Reactive printing urea substitute and preparation method thereof

    CN109594364A

  • High-permeability digital jet printing process for dark-color viscose silk fabric

    CN112080955A

  • Urea substitute with low ammonia and nitrogen and high color yield and reactive printing method thereof

    CN112323514A

  • Active ink digital printing pretreating size for woolen fabric

    CN105926319A

  • Color fastness reinforcing agent for dyeing cotton ramie blended yarns

    CN107254789A